HUBUNGAN MOTIVASI DENGAN PELAKSANAAN DISCHARGE PLANNING PADA PERAWAT DI RUANG RAWAT INAP BAGIAN INTERNIS TAHUN 2015 - Indra Hizkia Perangin-angin (Elisabeth Health Jurnal, 2016)
Characteristics nurse who has always been a determinant of the direction and strength work is motivation. Motivation is a feeling or thought that drives someone to do a job or running power, especially in the act. Discharge planning is a process of commencement of patient health services followed with continuity of care both in the healing process as well as in maintaining the health status until the patient feels ready to return to the environment. Goal: This study aims to determine the motivation is there any relation with the implementation of Discharge Planning in Space inpatient part internist Santa Elisabeth Hospital Medan. Method: Design Cross-sectional study. Population is a nurse working in the inpatient unit of internal RSE Nonrandom Sampling method (Non-probability) that as many as 51 people. Data collection techniques used by technical questionnaire given to nurses in the inpatient unit internist. Result: Frequency distribution of motivation (58.8%) experienced an increase in the frequency and distribution of discharge planning implementation there (88.2%). There is no significant relationship between motivation with the implementation of discharge planning by using Spearman Rank test, based on the data analysis could value P value equal to 0.088> 0.05. Expected to nurses to be optimal to perform discharge planning in the room internist Santa Elisabeth Hospital Medan and Nurses have the opportunity to attend seminars, workshops, conferences, lokarya and so on discharge planning.